2016
DOI: 10.18632/oncotarget.10550
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of kinase insert domain receptor by cyclin-dependent kinase 5 at serine 229 is associated with invasive behavior and poor prognosis in prolactin pituitary adenomas

Abstract: Pituitary adenomas constitute 15-20% of intracranial neoplasms. Previously we reported that cyclin-dependent kinase 5 (CDK5) is upregulated in pituitary tumors associated with activating protein p35, and plays an essential role in pituitary adenomas progression. Here we explored the mechanisms of CDK5 signaling in prolactin pituitary adenomas. Our data indicate that p35 expression and CDK5 activity are both significantly increased in human invasive prolactin pituitary adenomas as compared to noninvasive forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…Second, mRNA and protein expression levels of Cdk5 and its activators are increased, or decreased, in several forms of cancer and these alterations are correlated with cancer severity (Figure 1a, Key Figure; Table 1). For example, Cdk5 and p35/p25 are elevated in pulmonary neuroendocrine cancers [911], in sporadic and familial forms of medullary thyroid carcinoma (MTC) [12] and pituitary adenoma [13]. In fact Cdk5 and p35/p25 expression appear to typify neuroendocrine cancer pathology.…”
Section: Human Cancers Express Cdk5mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, mRNA and protein expression levels of Cdk5 and its activators are increased, or decreased, in several forms of cancer and these alterations are correlated with cancer severity (Figure 1a, Key Figure; Table 1). For example, Cdk5 and p35/p25 are elevated in pulmonary neuroendocrine cancers [911], in sporadic and familial forms of medullary thyroid carcinoma (MTC) [12] and pituitary adenoma [13]. In fact Cdk5 and p35/p25 expression appear to typify neuroendocrine cancer pathology.…”
Section: Human Cancers Express Cdk5mentioning
confidence: 99%
“…Cdk5 activity drives the migration and metastatic invasion of some forms of lung [42], prostate [29, 43], pancreas [6, 44], melanoma [45], pituitary [13] and thyroid [27] cancers. The migration of these cancer cells in culture or in vivo is stopped upon Cdk5 inhibition (Figure 2c).…”
Section: Cdk5 and Cancer Disseminationmentioning
confidence: 99%
“…CDK5 is speci cally activated in human prolactinomas (14), and the pituitary has high levels of Pit-1.…”
Section: Resultsmentioning
confidence: 99%
“…CDK5 is not activated by cyclins but by its activators p35 and p39 (11,12), whose constitutive expression is largely restricted to cells of neural crest origin. Our group found for the rst time that CDK5 exists in normal human pituitary and pituitary adenomas and found that CDK5 can promote the growth and invasion of pituitary adenomas (13,14), but the true regulatory mechanism of CDK5 in pituitary tumors is far from clear; speci cally, it is unknown whether CDK5 is involved in the regulation of hormone synthesis, secretion, and apoptosis in prolactinoma, which requires in-depth research.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated levels of CDK5 have been found in various mouse tumors and human malignant tumors [40] [53, 6265]. The mechanisms involve effects on angiogenesis, cell proliferation and the immune system.…”
Section: Cdk5 Expression In Cancermentioning
confidence: 99%